2021
DOI: 10.2217/pme-2020-0120
|View full text |Cite
|
Sign up to set email alerts
|

Deliberations About Clinical Pharmacogenetic Testing in Pediatric Oncology

Abstract: This article summarizes the background, content and outcomes of a special meeting that was convened among oncologists and scientists to discuss the role of pharmacogenetic (PGx) testing in pediatric clinical oncology practice. This meeting provided an opportunity for what the lead author (AM Issa) refers to as the ‘voice of the clinician’ dynamic to be amplified in order to better understand how personalized or precision medicine applications such as PGx testing are adopted and incorporated into clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This ongoing concern has been documented amongst primary care providers (Haga et al, 2012a), general pediatricians (Rahawi et al, 2020), cardiologists (Deininger et al, 2019), pharmacists (McMahon & Tucci, 2011), and recently in pediatric oncologists (Issa et al, 2021). Guidance is available; CPIC curates information on specific gene and drug pairs (Clinical Pharmacogenetics Implementation Consortium, 2019), and implementation initiatives are ongoing, especially with regard to looking at the use of the electronic medical record to aid clinician decision support (Cavallari et al, 2019; Dunnenberger et al, 2015; Hoffman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ongoing concern has been documented amongst primary care providers (Haga et al, 2012a), general pediatricians (Rahawi et al, 2020), cardiologists (Deininger et al, 2019), pharmacists (McMahon & Tucci, 2011), and recently in pediatric oncologists (Issa et al, 2021). Guidance is available; CPIC curates information on specific gene and drug pairs (Clinical Pharmacogenetics Implementation Consortium, 2019), and implementation initiatives are ongoing, especially with regard to looking at the use of the electronic medical record to aid clinician decision support (Cavallari et al, 2019; Dunnenberger et al, 2015; Hoffman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most providers including current fellows felt they did not receive sufficient PGx training and most reported mixed feelings regarding ordering, interpreting, and talking about PGx testing with their patients, as well as mixed feelings about the current state of knowledge about PGx testing with regard to implementing services now versus in the future. This ongoing concern has been documented amongst primary care providers (Haga et al, 2012a), general pediatricians (Rahawi et al, 2020), cardiologists (Deininger et al, 2019), pharmacists (McMahon & Tucci, 2011, and recently in pediatric oncologists (Issa et al, 2021). Guidance is available; CPIC curates information on specific gene and drug pairs (Clinical Pharmacogenetics Implementation Consortium, 2019), and implementation initiatives are ongoing, especially with regard to looking at the use of the electronic medical record to aid clinician decision support (Cavallari et al, 2019;Dunnenberger et al, 2015;Hoffman et al, 2014).…”
Section: Providers Still Lack Awareness Of Pgx Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional differences between children and adults related to behavioral and environmental impacts on disease and therapeutic goals [18,19] further complicate the use of adult-trialed therapies in children. Another prominent theme was the notion of increased phenotypic heterogeneity in children compared to adults; namely, children have natural genetic variations that often change throughout their development, impacting gene expression and possibly gene function [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Moreover, these differences may not only exist between children and adults, but also across the developmental trajectory between infants, children, and adolescents [19,21,22,35].…”
Section: Children Are a Unique Populationmentioning
confidence: 99%
“…The literature suggests that the healthcare providers were also generally accepting and enthusiastic toward precision health interventions [32,34,59,67] and reported that the quality of scientific evidence, clinical benefit to the child, family preferences, hope for children where no hope existed previously, and their sense of satisfaction with the care were all important in their decision making to utilize precision health interventions [61,62,77]. Despite this enthusiasm, there were also some opposing views about the application of pharmacogenomic testing.…”
Section: Stakeholder Preferences and Valuesmentioning
confidence: 99%